2019
DOI: 10.1101/718940
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A genome-wide CRISPR screen identifies ZCCHC14 as a host factor required for hepatitis B surface antigen production

Abstract: A hallmark of chronic hepatitis B virus (CHB) infection is the presence of high circulating levels of non-infectious small lipid HBV surface antigen (HBsAg) vesicles. Although rare, sustained HBsAg loss is the idealized endpoint of any CHB therapy. A novel small molecule RG7834 has been previously reported to inhibit HBsAg expression by targeting terminal nucleotidyltransferase protein 4A and 4B (TENT4A and TENT4B). In this study, we describe a genome-wide CRISPR screen to identify other potential novel host f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 47 publications
1
25
3
Order By: Relevance
“…2C). RG7834 also inhibited PAPD5, although the potency (IC50 = 167 nM) was lower than previously reported (IC50 = 1.3 nM) (31), possibly due to the more truncated PAPD5 form that was used in the current study. AB-452 and RG7834 inhibited PAPD7 enzymatic activity with IC50 values of 498 nM and 1093 nM, respectively.…”
Section: Ab-452 Promotes Hbv Rna Degradation Through Inhibiting Papd5/7 and Blocking Guanosine Incorporation Within Hbv Poly(a) Tailscontrasting
confidence: 81%
See 1 more Smart Citation
“…2C). RG7834 also inhibited PAPD5, although the potency (IC50 = 167 nM) was lower than previously reported (IC50 = 1.3 nM) (31), possibly due to the more truncated PAPD5 form that was used in the current study. AB-452 and RG7834 inhibited PAPD7 enzymatic activity with IC50 values of 498 nM and 1093 nM, respectively.…”
Section: Ab-452 Promotes Hbv Rna Degradation Through Inhibiting Papd5/7 and Blocking Guanosine Incorporation Within Hbv Poly(a) Tailscontrasting
confidence: 81%
“…Using a genome-wide CRISPR screen, it was subsequently observed that ZCCHC14 and PAPD5 were essential for the antiviral activity of RG7834 (31). Interestingly, individual knockdown of PAPD5 or PAPD7 had minimal effect against HBsAg production, while knockdown of ZCCHC14 or double knockdown of PAPD5/7 had a profound anti-HBsAg activity similar to that observed when cells were treated with RG7843 (31,36).…”
Section: Introductionmentioning
confidence: 86%
“…However, the ways in which TENT4A and TENT4B select their mRNA targets, presumably in the nucleus, remain to be established. Consistent with the potential stabilizing role of TENT4A/B is the observation that TENT4A and TENT4B stabilize viral RNA that is transcribed from hepatitis B virus (HBV) and human cytomegalovirus (HCMV) through the mixed tailing of their poly(A) (Hyrina et al, 2019; Kim et al, 2020; Mueller et al, 2019). This process occurs independently of other components of the TRAMP complex (i.e., zinc finger CCHC domain‐containing protein 7 [ZCCHC7] and hMTR4).…”
Section: Noncanonical Polyadenylationmentioning
confidence: 84%
“…Further research is needed to resolve this issue. TENT4A/B acts in complex with other proteins (e.g., TRAMP) to target RNA for exosome‐mediated degradation (Fasken et al, 2011; LaCava et al, 2005) but can also be recruited to other substrates, such as viral RNAs, by ZCCHC14 (Hyrina et al, 2019; Kim et al, 2020). TUT4/7 substrate specificity is highly dependent on the molecular context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation